Aplikasi Game Quiz Animals Berbasis Windows 8 - Yulyani Arifin; Budi Handoko; Venansius Kevin Nurtanio (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Game is currently in great demand by various circles, especially children. Children's interest in the game can be used as a tool to increase children’s intellectuality, i.e. English competence. The purpose of this study is to design an animal-themed quiz game in English languange based on Windows 8 operating system, followed by making a game prototype designed. This game is expected to be an exciting educational tool for children in learning English and broadening the knowledge about types of animal. The research is conducted through the stages of game design requirements, game design, evaluation and implementation. Based on theresults of the evaluation it is found that thoroughly the game already meets the standards of IMK by Shneiderman and Plaisant (2010). It is good enough as a game play since it is available at Window Store.